2014
DOI: 10.1039/c3qi00053b
|View full text |Cite
|
Sign up to set email alerts
|

Pt/Ru/C nanocomposites for methanol electrooxidation: how Ru nanocrystals’ surface structure affects catalytic performance of deposited Pt particles

Abstract: The surface structure of supporting materials has great effect on the catalytic performance of supported catalysts. In this work, three kinds of Ru nanocrystals with different morphologies and surface structures, namely triangular plates (TPs), capped columns (CCs) and nanospheres (NSs), were used as substrates for the deposition of Pt particles through an aqueous adsorption-reduction approach. By testing the catalytic activity and stability of these composite catalysts towards methanol electrooxidation, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
(62 reference statements)
1
11
0
Order By: Relevance
“…In conclusion, one could note that microwave irradiation increases the catalyst activity. 26 Comparing the activity of M-PtRu@C and M-Pt@C catalysts, one can see that the addition of the Ru improves MOR activity as previously reported in the literature. Chronoamperomograms were taken of these catalysts in 0.5 M H 2 SO 4 + 1.0 M CH 3 OH solution at 0.6 V ( Figure 6).…”
Section: Electrochemical Measurementssupporting
confidence: 73%
See 3 more Smart Citations
“…In conclusion, one could note that microwave irradiation increases the catalyst activity. 26 Comparing the activity of M-PtRu@C and M-Pt@C catalysts, one can see that the addition of the Ru improves MOR activity as previously reported in the literature. Chronoamperomograms were taken of these catalysts in 0.5 M H 2 SO 4 + 1.0 M CH 3 OH solution at 0.6 V ( Figure 6).…”
Section: Electrochemical Measurementssupporting
confidence: 73%
“…Similarly, Gu et al reported that by the addition of Ru MOR activity of Pt particles was enhanced at different levels by introducing Ru nanoparticles. 26 M-PtRu@C catalyst showed the highest initial current and the highest current at the longer time, confirming that this catalyst had higher electrocatalytic activity and higher resistance to CO. Depending on these CA measurements, the turnover number (TON), the number of methanol molecules that react per catalyst surface site per second, was calculated by using the following equation: 40 T ON (molecules/s.site) = [I(mA/cm…”
Section: Electrochemical Measurementsmentioning
confidence: 67%
See 2 more Smart Citations
“…The high index structure of the dendritic shell may allow for rearrangement and dissolution during the oxidation and reduction cycles due to its higher surface area and less stable facets compared to the low index facets of the cuboctahedral shell. 37…”
Section: Physical Chemistry Chemical Physics Accepted Manuscriptmentioning
confidence: 99%